Diferentes soluciones nutritivas en sistema hidroponico en el comportamiento de tres variedades de lechuga (Lactuca sativa) en Santo Domingo - Moreno Medina, Hugo Javier (2015)
This research was made in the province of Santo Domingo de los Tsáchilas, Canton Santo Domingo de los Colorados, Parish Chiguilpe in the field of housing tax Montufar Battalion , Road to Quito Km 8 , whose geographical coordinates are 0 °16' 24 ' south latitude and 79 ° 0,5'55 " west longitude at an altitude of 656 msnm, rainfall precipitation is 3100mm / year , temperature 21 -26ºC , aimed at evaluating the different nutrient solutions in hydroponics system behavior three varieties of lettuce ( Lactuca sativa ). Design was used completely randomized ( CRD) with 4 treatments and 4 replicates job was to analyze the media 's multiple range test of Duncan at 95 % probability was applied , the treatments were T1 ( Nutrient solution A and C ( 5cc / L H2O) + B ( 2cc / L H2O) 50% ) , T2 ( nutrient solution A and C ( 5cc / L H2O) + B ( 2cc / L H2O ) 75 % ) , T3 (Solution A nutritious and C ( 5cc / L H2O) + B ( 2cc / L H2O ) to 100% ) and T4 ( 5cc liquid Humus / L H2O). Design was used completely randomized The treatment T3 ( Nutrient solution A and C ( 5cc / L H2O) + B ( 2cc / L H2O ) at 100% ) , obtained better results when measuring the variables with more weight, more leaves , root length , improved profitability and utility at the time of harvest, followed by treatment T2 ( nutrient solution a and C ( 5cc / L H2O) + B ( 2cc / L H2O ) 75 %)